Corporate Bond Risk and Real Activity : An Empirical Analysis of Yield Spreads and Their Systematic Components - Ivaschenko, Iryna (IMF Working Papers; Working Paper, 2001)
This paper finds that the yield spread of investment-grade bonds relative to Treasuries, a proxy of default risk, predicts marginal changes in industrial production in the United States up to 12 months in the future, even upon controlling for a commonly used predictor such as the commercial paper spread. The paper also finds that systematic risk factors associated with the yield spread of investment-grade bonds to a variety of risk-free benchmarks - Treasuries, agency bonds, and AAA-rated bonds - have significant predictive content for future growth rate of industrial production at 3 to 18 months forecasting horizon, both in- and out-of-sample. Finally, a regime-switching estimation shows that the systematic risk component is also able to capture "industrial production business cycle" well.